Readiness of European laboratories for the revised EU Ambient Air Quality Directive: An interlaboratory comparison on levoglucosan, mannosan and galactosan in PM2.5 - Falk Mothes; Laurent Poulain; Jean-Luc Jaffrezo; Sophie Darfeuil; Rhabira Elazzouzi; Karl Espen Yttri; Hans Gundersen; Nicolas Bonnaire; Jean-Eudes Petit; Benjamin Bergmans; Eric Moïs; Theodoros Potouridis; et al. (Atmospheric Environment, 2026)

The carbon dioxide radical anion as a reductant in water treatment and atmospheric chemistry: a review - Thomas Schaefer; Jonathan D. Raff; Mallikarjuna N. Nadagouda; Eric Lichtfouse; Dan Meyerstein; Hartmut Herrmann; Virender K. Sharma (Environmental Chemistry Letters, 2026)
The carbon dioxide radical anion, CO 2 ●− , is a highly reactive radical species involved in the reduction of the CO 2 greenhouse gas, organic synthesis, atmospheric aerosol chemistry, and treatment of halogenated compounds. In recent years, CO 2 ●− has emerged as a strong reductant, or single electron donor. Here we present techniques used to generate CO 2 ●− and we discuss applications to degrading pollutants such as halogenated alkanes. The potential occurrence of such reductions in water and aqueous aerosols is discussed, notably for the degradation of perfluoroalkyl substances. In the laboratory, CO 2 ●− is directly generated by either direct electrochemical reduction of CO 2 or hydrogen atom transfer of either formate salts with and without catalysts or ferrioxalate through photochemical or radiolytic processes. The CO 2 ●− has an ultraviolet spectrum, and CO 2 ●− vibration modes are characterized by fast kinetics using infrared and Raman spectroscopy. The second-order rate constants of the reactions of CO 2 ●− with halogenated alkanes, of -1.84 ± 0.22 V, are generally slower than that of the hydrated electron, of -2.87 V, and give a negative linear relationship with energy of lower unoccupied molecular orbital, suggesting single electron transfer mechanism in reducing the halogenated compounds.

Corrigendum to “The pressure balancing act in geological storage: sharing the subsurface for the common good” [Int. Journal of Greenhouse Gas Control 151 (2026) 104610] - Audrey Ougier-Simonin; Owain Tucker; Alexander Bump; Sarah E. Gasda; Rannveig Elise Otterlei; Adriana Lemgruber-Traby; Eric Mackay; Ludovic Paul Ricard; Felix Herrmann; Matthias Imhof (International Journal of Greenhouse Gas Control, 2026)

The pressure balancing act in geological storage: sharing the subsurface for the common good - Audrey Ougier-Simonin; Owain Tucker; Alexander Bump; Sarah Eileen Gasda; Rannveig Elise Otterlei; Adriana Lemgruber-Traby; Eric Mackay; Ludovic Paul Ricard; Felix Herrmann; Matthias Imhof (International Journal of Greenhouse Gas Control, 2026)

Integrating animals, pasture, and crops within AusFarm for modelling mixed farming - Neville I. Herrmann; Andrew D. Moore; Eric Zurcher (Environmental Modelling & Software, 2024)

The impact of a massive wildfire event on avian species richness and abundance in an arid African savanna ecosystem - Alan T.K. Lee; Eric Herrmann; Ernst F. Retief; Ester van der Westhuizen-Coetzer; Colleen L. Seymour (Journal of Arid Environments, 2023)

Building the information system of the French Critical Zone Observatories network: Theia/OZCAR-IS - Isabelle Braud; Véronique Chaffard; Charly Coussot; Sylvie Galle; Patrick Juen; Hugues Alexandre; Philippe Baillion; Annick Battais; Brice Boudevillain; Flora Branger; Guillaume Brissebrat; Rémi Cailletaud; et al. (Hydrological Sciences Journal, 2022)

Regional Gas Transport During Conventional and Oscillatory Ventilation Assessed by Xenon-Enhanced Computed Tomography - Jacob Herrmann; Sarah E. Gerard; Joseph M. Reinhardt; Eric A. Hoffman; David W. Kaczka (Annals of Biomedical Engineering, 2021)

Genome‐inferred spatio‐temporal resolution of an uncultivated Roizmanbacterium reveals its ecological preferences in groundwater - Patricia Geesink; Carl‐Eric Wegner; Alexander J. Probst; Martina Herrmann; Hang T. Dam; Anne‐Kristin Kaster; Kirsten Küsel (Environmental Microbiology, 2020)
Summary Subsurface ecosystems like groundwater harbour diverse microbial communities, including small‐sized, putatively symbiotic organisms of the Candidate Phyla Radiation, yet little is known about their ecological preferences and potential microbial partners. Here, we investigated a member of the superphylum Microgenomates ( Cand . Roizmanbacterium ADI133) from oligotrophic groundwater using mini‐metagenomics and monitored its spatio‐temporal distribution using 16S rRNA gene analyses. A Roizmanbacteria‐specific quantitative PCR assay allowed us to track its abundance over the course of 1 year within eight groundwater wells along a 5.4 km hillslope transect, where Roizmanbacteria reached maximum relative abundances of 2.3%. In‐depth genomic analyses suggested that Cand . Roizmanbacterium ADI133 is a lactic acid fermenter, potentially able to utilize a range of complex carbon substrates, including cellulose. We hypothesize that it attaches to host cells using a trimeric autotransporter adhesin and inhibits their cell wall biosynthesis using a toxin–antitoxin system. Network analyses based on correlating Cand . Roizmanbacterium ADI133 abundances with amplicon sequencing‐derived microbial community profiles suggested one potential host organism, classified as a member of the class Thermodesulfovibrionia (Nitrospirae). By providing lactate as an electron donor Cand . Roizmanbacterium ADI133 potentially mediates the transfer of carbon to other microorganisms and thereby is an important connector in the microbial community.

Feedbacks underlie the resilience of salt marshes and rapid reversal of consumer‐driven die‐off - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Eric E. Axelman; Nicholas C. Herrmann; P. Lauren Szathmary (Ecology, 2013)
Understanding ecosystem resilience to human impacts is critical for conservation and restoration. The large‐scale die‐off of New England salt marshes was triggered by overfishing and resulted from decades of runaway crab grazing. In 2009, however, cordgrass began to recover, decreasing die‐off ∼40% by 2010. We used surveys and experiments to test whether plant–substrate feedbacks underlie marsh resilience. Initially, grazer‐generated die‐off swept through the cordgrass, creating exposed, stressful peat banks that inhibited plant growth. This desertification cycle broke when banks eroded and peat transitioned into mud with fewer herbivores, less grazing, and lower physical stress. Cordgrass reestablished in these areas through a feedback where it engineered a recovery zone by further ameliorating physical stresses and facilitating additional revegetation. Our results reveal that feedbacks can play a critical role in rapid, reversible ecosystem shifts associated with human impacts, and that the interplay of facilitative and consumer interactions should be incorporated into resilience theory.

Development of polymorphic microsatellite loci for the rattlesnake species Crotalus atrox, C. cerastes, and C. scutulatus (Viperidae: Crotalinae) and cross-species amplification of microsatellite markers in Crotalus and Sistrurus species - Krystyn Pozarowski; D. Suzi Bryan; Rebekah Bosse; Eric Watson; Hans-Werner Herrmann (Conservation Genetics Resources, 2012)